Noninvasive cardiac-specific biomarkers for the diagnosis and prevention of vascular stenosis in cardiovascular disorder - Pulukool, Sujith Kumar; Srimadh Bhagavatham, Sai Krishna; Vijay, Sudarshan K.; Almansour, Abdulrahman I.; Chaudhary, Sandeep; Abuyousef, Farah; Saleh, Na’il; Tripathi, Pratima (Frontiers in Pharmacology, 2024)
Background: The most frequent lesion in the blood vessels feeding the myocardium is vascular stenosis, a condition that develops slowly but can prove to be deadly in a long run. Non-invasive biomarkers could play a significant role in timely diagnosis, detection and management for vascular stenosis events associated with cardiovascular disorders. Aims: The study aimed to investigate high sensitivity troponin I (hs-TnI), cardiac troponin I (c-TnI) and high sensitivity C-reactive protein (hs-CRP) that may be used solely or in combination in detecting the extent of vascular stenosis in CVD patients. Methodology: 274 patients with dyspnea/orthopnea complaints visiting the cardiologists were enrolled in this study. Angiographic study was conducted on the enrolled patients to examine the extent of stenosis in the five prominent vessels (LDA, LCX, PDA/PLV, RCA, and OM) connected to the myocardium. Samples from all the cases suspected to be having coronary artery stenosis were collected, and subjected to biochemical evaluation of certain cardiac inflammatory biomarkers (c-TnI, hsTn-I and hs-CRP) to check their sensitivity with the level of vascular stenosis. The extent of mild and culprit stenosis was detected during angiographic examination and the same was reported in the form significant (≥50% stenosis in the vessels) and non-significant (<50% stenosis in the vessels) Carotid Stenosis. Ethical Clearance for the study was provided by Dr. Ram Manohar Lohia Institute of Medical Sciences Institutional Ethical Committee. Informed consent was obtained from all the participants enrolled in the study. Results: We observed that 85% of the total population enrolled in this study was suffering from hypertension followed by 62.40% detected with sporadic episodes of chest pain. Most of the subjects (42% of the total population) had stenosis in their LAD followed by 38% who had stenosis in their RCA. Almost 23% patients were reported to have stenosis in their LCX followed by OM (18% patients), PDA/PLV (13%) and only 10% patients had blockage problem in their diagonal. 24% of the subjects were found to have stenosis in a single vessel and hence were categorized in the Single Vessel Disease (SVD) group while 76% were having stenosis in two or more than two arteries (Multiple Vessel Disease). hs-TnI level was found to be correlated with the levels of stenosis and was higher in the MVD group as compared to the SVD group. Conclusion: hs-TnI could be used as a novel marker as it shows prominence in detecting the level of stenosis quite earlier as compared to c-TnI which gets detected only after a long duration in the CVD patients admitted for angiography. hs- CRP gets readily detected as inflammation marker in these patients and hence could be used in combination with hs-TnI to detect the risk of developing coronary artery disease.